Long non-coding RNAs in cancer and development: where do we go from here? - Hämmerle, Monika; Gutschner, Tony (International journal of molecular sciences, 2015)
Recent genome-wide expression profiling studies have uncovered a huge amount of novel, long non-protein-coding RNA transcripts (lncRNA). In general, these transcripts possess a low, but tissue-specific expression, and their nucleotide sequences are often poorly conserved. However, several studies showed that lncRNAs can have important roles for normal tissue development and regulate cellular pluripotency as well as differentiation. Moreover, lncRNAs are implicated in the control of multiple molecular pathways leading to gene expression changes and thus, ultimately modulate cell proliferation, migration and apoptosis. Consequently, deregulation of lncRNA expression contributes to carcinogenesis and is associated with human diseases, e.g., neurodegenerative disorders like Alzheimer’s Disease. Here, we will focus on some major challenges of lncRNA research, especially loss-of-function studies. We will delineate strategies for lncRNA gene targeting in vivo, and we will briefly discuss important consideration and pitfalls when investigating lncRNA functions in knockout animal models. Finally, we will highlight future opportunities for lncRNAs research by applying the concept of cross-species comparison, which might contribute to novel disease biomarker discovery and might identify lncRNAs as potential therapeutic targets.